(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: Dentin hypersensitivity is a common oral health problem, which is of great concern in the world and in Vietnam. Objective: Determination of prevalence, clinical characteristics and related factors of dentin hypersensitivity of workers exposed to acids. Methods: Cross-sectional study. Results: This study collected information from 868 workers exposed to acids in Lam Thao Super Phosphate and Chemical Joint Stock Company through questionnaires and examination and assessment of hurt related to dentin hypersensitivity. The research results show that the rate of dentin hypersensitivity in workers exposed to acid was 59.7%, of which molar group accounted for 60.0%.